2012
DOI: 10.1038/nature11124
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional limb joint mobility in the early tetrapod Ichthyostega

Abstract: The origin of tetrapods and the transition from swimming to walking was a pivotal step in the evolution and diversification of terrestrial vertebrates. During this time, modifications of the limbs—particularly the specialization of joints and the structures that guide their motions—fundamentally changed the ways in which early tetrapods could move. Nonetheless, little is known about the functional consequences of limb anatomy in early tetrapods and how that anatomy influenced locomotion capabilities at this ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
258
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(272 citation statements)
references
References 24 publications
13
258
1
Order By: Relevance
“…Our discovery that the evolution of larger eye sockets occurred in animals that were primarily aquatic is in line with other critical conclusions of the past several decades of early tetrapod paleontology, which has found that robust limbs evolved in primarily aquatic animals (9,10) and that fingers and toes evolved in primarily aquatic animals (11). Notably, the increase in eye size starting in the elpistostegalians coincided with a distinct change in the placement of eyes in this group.…”
Section: Significancesupporting
confidence: 70%
See 1 more Smart Citation
“…Our discovery that the evolution of larger eye sockets occurred in animals that were primarily aquatic is in line with other critical conclusions of the past several decades of early tetrapod paleontology, which has found that robust limbs evolved in primarily aquatic animals (9,10) and that fingers and toes evolved in primarily aquatic animals (11). Notably, the increase in eye size starting in the elpistostegalians coincided with a distinct change in the placement of eyes in this group.…”
Section: Significancesupporting
confidence: 70%
“…This big increase in eye size was likely driven by aquatic tetrapods surfacing their eyes above the water line and hunting like crocodiles. This lifestyle caused "primarily aquatic" features to be retained (9,11,68), while more and more robust limbs gradually evolved, enabling forays onto land (69). Because small adjustments to optical mechanics evolved to account for the change in the refractive index of air from water, there was an ever-expanding domain of visual awareness, leading these animals to long-range viewing and hunting of the bounty of invertebrate food on the shores.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of character transformations in the pectoral appendicular skeleton that accompanied the fins-to-limbs and water-to-land transitions in tetrapods has been described in detail (e.g. Coates, Jeffery & Ruta, 2002;Shubin, Daeschler & Coates, 2004;Hall, 2008;Boisvert, 2009;Callier, Clack & Ahlberg, 2009;Ahlberg, 2011;Pierce, Clack & Hutchinson, 2012). Changes between tetrapodomorph fish such as Eusthenopteron and Devonian tetrapods such as Acanthostega include the following: in the shoulder girdle, dermal bones spanning the head-trunk boundary were lost and the endoskeletal girdle was enlarged (Coates et al, 2002;, and the orientation of the shoulder joint (glenoid) changed from posterior to posterolateral.…”
Section: Introductionmentioning
confidence: 99%
“…The radius and ulna transformed from flattened, diverging elements of unequal length to two parallel cylinders articulating distally with multiple carpal bones (Andrews & Westoll, 1970a;Ahlberg, 2011 skeleton lost its dermal fin rays (lepidotrichia) and gained digits. Functionally, these changes led to the pectoral limb becoming a weight-bearing appendage directed laterally rather than posteriorly (Boisvert, Mark-Kurik & Ahlberg, 2008) with restricted shoulder rotation Pierce et al, 2012;Pierce, Hutchinson, & Clack, 2013), and a flexed elbow (Ahlberg, 2011). Reconstructions of soft tissue anatomy are equally important as those of the skeleton because they can provide crucial information about locomotion, mode of life, and ecology of extinct animals (Witmer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…While the evolutionary mechanism remains controversial, it is thought that the origin of the autopod lies early within Sarcopterygii where homologies to a modern digit bearing autopod can be seen in Devonian stem tetrapods, Acanthostega and Ichthyostega, that appeared around 360 Ma [27][28][29][30]. Like their predecessors, these species were probably entirely aquatic as their limbs lacked flexion at the joints that would be later required for supporting body weight on land [31].…”
Section: Origin Of the Tetrapod Autopodmentioning
confidence: 99%